Analisis Kredit dan Kredit Macet terhadap Bunga pada Bank Perkreditan Rakyat - Maesaroh, Siti; Asnaini, Sri Wahyuni (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
This research aims to analyze Loans and Bad Credit on Interest at Rural Banks. By using descriptive quantitative methods, it is hoped that this research will be able to answer the objectives and have benefits for future users of this research. Sampling is carried out using probability sampling techniques which provide equal opportunities for each member of the selected population. In this technique, sampling is carried out randomly according to proportions. So the number of samples in this research is the number of Rural Banks in the DKI Jakarta province and Banten province of 79 units. The research results show the influence of each variable, namely the bad credit variable does not have a significant influence on the interest variable, while the credit variable does not have any effect on bad credit, so the customer's understanding of large and small loans will not affect the condition of bad credit received while the interest charged to Borrowers are not the main factor in bad credit. Simultaneously the effect of the Bad Credit variable has no significant effect on Interest and the Credit variable has no significant effect on Interest. Then partially the variable Credit, Bad Credit has a significant effect on Interest. Based on qualitative analysis, the results show that people tend not to borrow at Rural Credit Banks due to knowledge, both interest, processes and the profits they can get when making transactions at Rural Credit Banks.